METHOD OF THE BLADDER PERFUSION IN ULTRASONIC DIAGNOSIS OF UROLITHIASIS OF DOMESTIC CATS - Кравченко, С. О. (Scientific Progress & Innovations, 2013)
Research has established that the use of perfusion of the bladder during ultrasound can increase the informativeness of diagnosis of urolithiasis in domestic cats. Introducing isotonic sodium chloride into the bladder provides its content and improves visualization of urolites and urinary sediment. In difficult cases (stones adhesion to the mucosa, empty bladder) this method improves the efficiency of diagnosis of disease.